2020
DOI: 10.1155/2020/8263408
|View full text |Cite
|
Sign up to set email alerts
|

Application of Femtosecond Laser in Anterior Segment Surgery

Abstract: Femtosecond laser (FSL) is a near-infrared laser that can create reliable and reproducible tissue cutting with minimal damage to adjacent tissue. As the laser can also create incisions with various orientations, depths, and shapes, it is expected to be a useful tool for anterior segment surgery, such as cornea, refractive, and cataract surgery. In this review, the authors will introduce the application of FSL in various anterior segment surgeries and discuss the results of studies regarding the efficacy and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 125 publications
0
31
0
Order By: Relevance
“…2 Despite the high rates of success, corneal transplantation is still complicated by relevant risks of intraoperative drawback, graft failure, and immunological complications. 3 For these reasons, in recent years, taking advantage of femtosecond laser (FSL) technology that allows precise and reproducible corneal cuts, 4 there has been a growing interest in stromal lenticule addition keratoplasty (SLAK) for the surgical treatment of advanced KC. The SLAK is a sutureless kind of keratoplasty which resumes the stromal keratophakia technique invented by Prof. Barraquer in 1960 and consists of the insertion of a lamella of the donor cornea inside a pocket sculpted into the host's stroma.…”
mentioning
confidence: 99%
“…2 Despite the high rates of success, corneal transplantation is still complicated by relevant risks of intraoperative drawback, graft failure, and immunological complications. 3 For these reasons, in recent years, taking advantage of femtosecond laser (FSL) technology that allows precise and reproducible corneal cuts, 4 there has been a growing interest in stromal lenticule addition keratoplasty (SLAK) for the surgical treatment of advanced KC. The SLAK is a sutureless kind of keratoplasty which resumes the stromal keratophakia technique invented by Prof. Barraquer in 1960 and consists of the insertion of a lamella of the donor cornea inside a pocket sculpted into the host's stroma.…”
mentioning
confidence: 99%
“…In reviewing the literature, we found that the use of the FLACS technique entails a learning curve [ 26 ]. Several studies have indicated increased safety after a learning curve [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The femtosecond laser is a neodymium glass laser employing ultrashort pulse durations that allows making corneal incisions at the desired depth. [ 62 ] Several previous studies have described the use of the femtosecond laser during DALK to create lamellar side cuts[ 63 64 65 66 ] and an intrastromal channel for the air injection. [ 67 68 69 ] To date, the additional costs associated with this technology do not seem justified by the gains in patient outcomes.…”
Section: K Ey I Ssues M ...mentioning
confidence: 99%